GUItar and FAgoo: Graphical interface for automata visualization, editing, and interaction - André Almeida (2010)
GUItar is a graphical environment for graph visualization, editing, and interaction, that specially focuses in finite automata dia- grams. The application incorporates mechanisms to facilitate the editing of these graphs. It also provides a style manager that allows the cre- ation of rich state and arc styles to be used in the drawing of its ob- jects. This style manager allows the system to cope with complex styles, broaden the application scope to graphical representations of other com- putational models like transducers or Turing machines. GUItar also has a foreign function call (FFC) mechanism for the easy integration of exter- nal modules and libraries like automata symbolic manipulators or graph drawing libraries. For automatic graph drawing we are developing FA- goo, a package that seeks to provide tools capable of finding pleasant graph drawings. FAgoo implements graph drawing algorithms that find embeddings which the user, with minimal manual changes, can adjust to its aesthetically taste. Both GUItar and FAgoo are on going projects licensed under GPL.